Transition to parenthood: the needs of parents in pregnancy and early parenthood - Ingram Jenny; Johnson Debbie; Deave Toity (BMC, 2008)
Abstract Background Pregnancy and the transition to parenthood are major adjustment periods within a family. Existing studies have asked parents, retrospectively, about their experience of antenatal education, mainly focusing on women. We sought to address this gap by asking first-time mothers and their partners about how they could be better supported during the antenatal period, particularly in relation to the transition to parenthood and parenting skills. Methods Purposive sampling was used to recruit 24 nulliparous women with a range of ages from two healthcare organisations in South-West England, 20 of whom had partners. Recruitment took place antenatally at around 28 weeks gestation. Semi-structured interviews were undertaken at home in the last trimester of pregnancy and between 3-4 months postpartum. Content analysis of the interview data was undertaken. Results Several common themes emerged from both the ante- and postnatal data, including support mechanisms, information and antenatal education, breastfeeding, practical baby-care and relationship changes. Knowledge about the transition to parenthood was poor. Women generally felt well supported, especially by female relatives and, for those who attended them, postnatal groups. This was in contrast to the men who often only had health professionals and work colleagues to turn to. The men felt very involved with their partners' pregnancy but excluded from antenatal appointments, antenatal classes and by the literature that was available. Parents had been unaware of, and surprised at, the changes in the relationship with their partners. They would have liked more information on elements of parenting and baby care, relationship changes and partners' perspectives prior to becoming parents. Conclusion Many studies and policy documents have highlighted the paucity of parents' preparation for parenthood. This study has indicated the need for an improvement in parents' preparation for parenthood, the importance of including fathers in antenatal education and that inadequate preparation remains a concern to both women and their partners. This paper identifies several avenues for action and further research to improve both new parents' experience of antenatal education and their preparation for parenthood.